Planar cell polarity protein Vangl2 interacts with M-cadherin and stabilizes its cell surface expression in mouse C2C12 myoblasts - Nagaoka, Tadahiro; Sasaki, Erina; Takagi, Sakiho; Kishi, Masashi; Hitachi, Keisuke; Tsuchida, Kunihiro (Frontiers in Cell and Developmental Biology, 2026)
Skeletal muscle regeneration depends on muscle stem cells (MuSCs), in which cadherin-mediated adhesion and planar cell polarity (PCP) signaling play critical roles. M-Cadherin is the major cadherin expressed in MuSCs; however, its functional link to PCP proteins remains unclear. In this study, we demonstrate that the PCP core component Vangl2 co-localizes with M-cadherin at the MuSC-myofiber boundary and directly interacts with it in C2C12 cells. Mutagenesis analyses revealed that the catenin-binding domain of M-cadherin and the C-terminal domain of Vangl2 are required for this interaction, which uniquely enables M-cadherin to form a ternary complex with Vangl2 and β-catenin. Knockdown of Vangl2 impaired myoblast fusion, reduced the expression of MyoD and Myomixer, and decreased the cell surface stability of M- and N-cadherins, while canonical Wnt/β-catenin and Akt signaling were unaffected. These findings demonstrate that Vangl2 stabilizes cadherins at the plasma membrane and promotes myogenic differentiation, suggesting a previously unrecognized role of PCP signaling in skeletal muscle maintenance and regeneration.